2017
DOI: 10.1111/vsu.12707
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for tibial damage associated with the modified Maquet technique in 174 stifles

Abstract: Based on these results, preventive measures against tibial damage associated with MMT should include: a thickness of cortical hinge based on the equation related to the BW; a length of osteotomy adjusted to the amount of TTA with an osteotomy angle below 10°; and slow advancement of the tibial tuberosity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 12 publications
1
9
0
1
Order By: Relevance
“…We decided not to include the development of intra-operative fissure at the hinge cortex into the postoperative minor complication rate count, but if this is was to be considered, our minor complication rate could be as high as 65.7% [ 21 ]. One study reported that only 9.4% of these fissures subsequently led to postoperative fractures [ 22 ]. In our cases, we presume that the development of a fissure of the cranial hinge cortex had a relatively benign outcome because of the protective effect exerted by the cerclage wire tension band that was applied intra-operatively in almost all cases.…”
Section: Discussionmentioning
confidence: 99%
“…We decided not to include the development of intra-operative fissure at the hinge cortex into the postoperative minor complication rate count, but if this is was to be considered, our minor complication rate could be as high as 65.7% [ 21 ]. One study reported that only 9.4% of these fissures subsequently led to postoperative fractures [ 22 ]. In our cases, we presume that the development of a fissure of the cranial hinge cortex had a relatively benign outcome because of the protective effect exerted by the cerclage wire tension band that was applied intra-operatively in almost all cases.…”
Section: Discussionmentioning
confidence: 99%
“…The implant we used was designed to advance the tibial tuberosity and to not exceed a distal angle of 11 degrees to approximate modified Maquet technique cut recommendations by Lefebvre and colleagues. 21 We also utilized a drill hole at the distal aspect of the osteotomy, as we have had good outcomes and minimal fissure/fracture complications with our previous experience performing a modified Maquet-tibial tuberosity advancement technique. 7 Despite these precautions, cortical hinge fractures occurred in 6/15 procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies suggested that reduced thickness of the osteotomized tibial tuberosity, incorrect plaque positioning, reduced contact of the osteotomy, wide angle of the preoperative patellar ligament, and iatrogenic region wounds during surgical dissection contribute to the development of this complication [8,17,18]. Lefebvre et al [24] stated that intraoperative fissures occurred more frequently than intraoperative fractures and were located most commonly at the distal aspect of the osteotomy line. They also considered the angle of opening of the osteotomy line and the thickness of the cortical hinge as the main factors increasing the risk of perioperative tibial damage during Maquet modified technique (MMT) in dogs [24].…”
Section: Discussionmentioning
confidence: 99%
“…Lefebvre et al [24] stated that intraoperative fissures occurred more frequently than intraoperative fractures and were located most commonly at the distal aspect of the osteotomy line. They also considered the angle of opening of the osteotomy line and the thickness of the cortical hinge as the main factors increasing the risk of perioperative tibial damage during Maquet modified technique (MMT) in dogs [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation